Associations of Adolescent Exposure to Severe Violence with Substance Use From Adolescence into Adulthood: Direct Versus Indirect Exposures. (28th January 2019) - Beharie, Nisha; Scheidell, Joy D.; Quinn, Kelly; McGorray, Susan; Vaddiparti, Krishna; Kumar, Pritika C.; Frueh, B. Christopher; Boone, Lauren; Khan, Maria R.
Abstract: Background: While previous research has documented the impact of violence on substance use, none has looked longitudinally across the lifespan to measure independent effects of direct and indirect violence exposure. Objective: To examine independent associations between adolescent experiences of violence and subsequent substance use in adolescence and adulthood in the United States. Method: Using the National Longitudinal Study of Adolescent to Adult Health ( N = 12, 288), we examined being shot or stabbed ("experienced"), being threatened with a knife or gun ("threatened"), and seeing someone either shot or stabbed ("witnessed") during adolescence (Wave I) as correlates of substance use in adolescence and adulthood (Wave IV) via logistic regression. Results: Violence exposure was a significant correlate of drug use in adolescence and several associations remained significant in adulthood. Witnessing violence had the highest point estimates in the adjusted models in adolescence for each substance use outcome (e.g., Cocaine-Adjusted Odds Ratios [AOR] = 2.59, 95% confidence interval [CI] = 1.21, 5.54). However, the point estimates for threatened with violence or experienced violence were highest in three out of the four drug outcomes in adulthood (e.g., Threatened with violence: Binge drinking-AOR = 1.41, 95% CI = 1.08, 1.83). Conclusion/Importance: Adolescent exposure to witnessing violence had stronger effects on substance use in adolescence, while experiencing and being threatened with violence in adolescence had stronger effects on substance use in adulthood. Violence prevention efforts targeted toward adolescents may lead to a reduction in substance use throughout the life-course, and clinicians and policy makers should be aware of the downstream effects of violence experienced in adolescence.